A Novel Hybrid Encryption Method to Secure Healthcare Data in IoT-enabled Healthcare Infrastructure. (July 2022) - Das, Sangjukta; Namasudra, Suyel
Highlights: A lightweight hybrid encryption scheme is proposed to improve the security of IoT-enabled healthcare infrastructure. Healthcare data is encrypted by using both symmetric and asymmetric encryption techniques. The integrity of healthcare data is ensured by using the elliptic curve-based digital signature. The security analysis and performance comparisons prove the effectiveness of the proposed scheme. Abstract: Nowadays, smart devices are playing a vital role to overtake the conventional healthcare management system. Here, the Internet of Things (IoT) leads the healthcare industry towards its expansion, where things can be connected anytime from anywhere, even in a heterogeneous environment. However, the security of healthcare data and preserving the privacy of users are major concerns in IoT-enabled healthcare infrastructure. This paper presents a novel encryption scheme using elliptic curve cryptography, Advanced Encryption Standard (AES), and Serpent to secure healthcare data in IoT-enabled healthcare infrastructure. This proposed hybrid encryption technique improves security measures of the healthcare data by incorporating both symmetric and asymmetric-based encryption techniques. Moreover, the proposed scheme also ensures data integrity by using the elliptic curve-based digital signature. To prove the efficiency of the proposed scheme, both formal security analysis and performance comparisons are presented in this paper. Results and discussion prove the effectiveness of the proposed scheme. Graphical Abstract: Image, graphical abstract